2002
DOI: 10.1101/gad.1014902
|View full text |Cite
|
Sign up to set email alerts
|

Mitotic-specific methylation of histone H4 Lys 20 follows increased PR-Set7 expression and its localization to mitotic chromosomes

Abstract: We describe distinct patterns of histone methylation during human cell cycle progression. Histone H4 methyltransferase activity was found to be cell cycle-regulated, consistent with increased H4 Lys 20 methylation at mitosis. This increase closely followed the cell cycleregulated expression of the H4 Lys 20 methyltransferase, PR-Set7. Localization of PR-Set7 to mitotic chromosomes and subsequent increase in H4 Lys 20 methylation were inversely correlated to transient H4 Lys 16 acetylation in early S-phase. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

28
203
2
3

Year Published

2004
2004
2014
2014

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 228 publications
(236 citation statements)
references
References 30 publications
28
203
2
3
Order By: Relevance
“…The chromatin association of L3MBTL1 mirrors the progressive accumulation of H4K20me1 during the cell cycle The H4K20me1 modification is cell cycle regulated although the timing of its appearance and peak levels have varied among different cell types and experimental strategies (Fang et al, 2002;Rice et al, 2002;Pesavento et al, 2008). Therefore, we examined the levels of L3MBTL1 during distinct phases of the cell cycle, and using synchronized K562 cells, we found high levels of L3MBTL1 protein in G1/S and S phase cells, but barely detectable levels in G2/M cells (not shown).…”
Section: Recognition Of Histone Methyl Lysines By L3mbtl1mentioning
confidence: 99%
“…The chromatin association of L3MBTL1 mirrors the progressive accumulation of H4K20me1 during the cell cycle The H4K20me1 modification is cell cycle regulated although the timing of its appearance and peak levels have varied among different cell types and experimental strategies (Fang et al, 2002;Rice et al, 2002;Pesavento et al, 2008). Therefore, we examined the levels of L3MBTL1 during distinct phases of the cell cycle, and using synchronized K562 cells, we found high levels of L3MBTL1 protein in G1/S and S phase cells, but barely detectable levels in G2/M cells (not shown).…”
Section: Recognition Of Histone Methyl Lysines By L3mbtl1mentioning
confidence: 99%
“…Another scenario could be that the hMOFdepleted cells may have a defective S phase checkpoint, therefore leading to the observed G 2 /M accumulation. We can speculate that a hMOF-dependent reduction of H4K16 acetylation, a modification that reaches its highest levels during mid-S phase (Rice et al, 2002), could affect DNA replication, as during this phase a tight co-ordination between DNA replication and preservation of epigenetic integrity must be achieved (Groth et al, 2007). An alternative explanation would be that loss of hMOF could impair the cell's ability to repair DNA, thereby activating the G 2 /M checkpoint.…”
Section: Hmof In the Dna Damage Responsementioning
confidence: 99%
“…HeLa cells were synchronized at the G 1 /S border by a thymidine-mimosine double block (31). Cells were released from the block and collected every 2.5 h, and then flow cytometry was used to determine their phase in the cell cycle (supplemental Fig.…”
Section: Global Changes In H4k20 Methylation Occur During Cell Cyclementioning
confidence: 99%
“…Although the loss of PR-Set7 by RNAi eventually resulted in defective replication fork activity and delayed S phase progression, several cell cycles were required to achieve this phenotype (29,30). Furthermore, we previously demonstrated that expression of PR-Set7 was tightly cell cycleregulated where it was undetectable at G 1 /S, slowly increased during late S phase, and peaked during mitosis, concomitant with its catalytic activity (31). Based on these contradictory observations, it currently remains unclear how PR-Set7 and H4K20 methylation function in mammalian cell cycle progression.…”
mentioning
confidence: 99%